Targeting the pathway of GSK-3β/nerve growth factor to attenuate post-infarction arrhythmias by preconditioned adipose-derived stem cells. (March 2017) - Lee, Tsung-Ming; Harn, Horng-Jyh; Chiou, Tzyy-Wen; Chuang, Ming-Hsi; Chen, Chun-Hung; Lin, Po-Cheng; Lin, Shinn-Zong
Abstract: Adipose-derived stem cell (ADSC) transplantation is a promising new therapy to improve cardiac function after myocardial infarction. However, its low efficacy of transdifferentiation hampers its usefulness. Glycogen synthase kinase-3β (GSK-3β) signal has been shown to play a role in preconditioning-induced cardioprotection. We assessed whether n- butylidenephthalide (BP) primed ADSCs can attenuate arrhythmias by a GSK-3β-dependent pathway after myocardial infarction. Male Wistar rats after coronary ligation was randomly allocated to receive intramyocardial injection of vehicle, ADSCs, BP-preconditioned ADSCs, (BP + lithium)-preconditioned ADSCs, (BP + SB216763)-preconditioned ADSCs, and (BP + LY294002)-preconditioned ADSCs. ADSCs were primed for 16 h before implantation. After 4 weeks of implantation, ADSCs were retained in myocardium, reduced fibrosis and improved cardiac function. Sympathetic hyperinnervation was blunted after administering ADSCs, assessed by immunofluorescent analysis, and Western blotting and real-time quantitative RT-PCR of nerve growth factor. Arrhythmic scores during programmed stimulation in the ADSC-treated infarcted rats were significantly lower than vehicle. BP-preconditioned ADSCs had superior cardioprotection, greater ADSC engraftment and transdifferentiation, and antiarrhythmic effects compared with ADSCs alone. Simultaneously, BP increased the levels of phospho-Akt and down-regulated GSK-3β activity. The effects of BP against sympathetic hyperinnervation were blocked by LY294002, a PI3K inhibitor. Addition of either lithium or SB216763 did not have additional effects compared with BP alone. Compared with ADSC alone, BP-primed ADSC implantation improved stem cell engraftment and attenuated sympathetic hyperinnervation and arrhythmias through a PI3K/Akt/GSK-3β-dependent pathway, suggesting that a synergic action was achieved between BP pretreatment and ADSCs. Highlights: Whether n- butylidenephthalide (BP)-primed ADSCs can attenuate arrhythmias is unknown. After 4 weeks of implantation, ADSCs administration attenuated arrhythmias. BP-preconditioned ADSCs had superior antiarrhythmic effects compared with ADSCs alone. The effects of BP against sympathetic hyperinnervation were blocked by LY294002. BP-primed ADSCs can attenuate arrhythmias by a GSK-3β-dependent pathway.